Pengaruh Anomali Pasar terhadap Return Saham Perusahaan LQ-45 - Allan Moechamad Zaennoer Kasdjan; Nazarudin .; Junaedi Yusuf (Universitas Swadaya Gunung Jati, 2017)
Abstract The debate about the concept of efficient markets are still common among experts until now. However emerged a number of new studies which suggested market anomaly which is a deviation from the concept of efficient markets. One kind of market anomalies is most often observed seasonal anomalies in this study consisted of the day of the week effect, week four effect, and the January effect. This research aims to determine whether there are significant market anomalies on stock return. The unit of analysis in this study is the daily stock return data LQ-45 from the date of July 1st, 2013 to June 30th , 2014. The sample in this research is secondary data and selected by using purposive sampling method. The sample of this research consist of 37 companies listed in index LQ-45 consistently in the period July 1st, 2013 to June 30th, 2014. The analysis method of this research used regression analysis with dummy variable.The result of this research showed that the day of the week effect didnt have negative significant effect to stock return, week four effect didnt have negative significant effect to stocks return, and Jauary effect didnt have positive significant effect to stock return. Keywords: Day Of The Week Effect; Week Four Effect; January Effect; Stock Return; Market Anomaly.Abstrak Perdebatan tentang konsep pasar yang efisien masih umum di kalangan para ahli sampai sekarang. Namun, kemunculan pasar anomali yang merupakan penyimpangan dari konsep pasar yang efisien. Salah satu jenis anomali pasar adalah anomali musiman yang paling sering diamati dalam penelitian ini yang terdiri dari efek hari minggu, efek minggu keempat, dan bulan Januari Efek Penelitian ini bertujuan untuk mengetahui apakah ada anomali pasar (efek hari minggu, efek minggu ke empat, pengaruh Januari) terhadap return saham. Unit analisis dalam penelitian ini adalah data return saham harian LQ-45 Dari tanggal 1 Juli 2013 sampai 30 Juni 2014. Penelitian ini memanfaatkan data sekunder dengan metode purposive sampling. Konsistensi LQ-45 pada periode 1 Juli 2013 sampai 30 Juni 2014. Metode analisis dalam penelitian ini adalah hasil dari penelitian ini Pengaruh efek minggu ini tidak berpengaruh negatif terhadap return saham, pengaruh minggu ke empat tidak memiliki Efek negatif terhadap return saham, dan efek January tidak berpengaruh positif terhadap return saham.Kata kunci: Day Of The Week Effect; Week Four Effect; January Effect;Stock Return; Anomali Pasar.